Enhanced elimination of Cr(VI) from aqueous media by polyethyleneimine modified corn straw biochar supported sulfide nanoscale zero valent iron: Performance and mechanism. (February 2023) - Tian, Haoran; Huang, Chao; Wang, Ping; Wei, Jie; Li, Xinyan; Zhang, Ruimei; Ling, Dingxun; Feng, Chongling; Liu, Hao; Wang, Mengxin; Liu, Zhiming
Graphical abstract: Highlights: A novel PEI modified biochar supported S-nZVI was successfully synthesized. The modification significantly improved the removal of Cr(VI) by nZVI. Cr(VI) removal mechanism by S-nZVI@PBC was elucidated. S-nZVI@PBC exhibits higher stability and reusability than nZVI. Abstract: A novel polyethyleneimine modified corn straw biochar supported sulfide nanoscale zero-valent iron (S-nZVI@PBC) was developed to enhance Cr(VI) removal from aqueous media. The characteristics of morphology, chemical composition, and functional groups of S-nZVI@PBC, as well as its kinetics and mechanism for Cr(VI) removal were explored. Characterization verified S-nZVI was successfully loaded onto PEI modified biochar. The adsorption process was well represented pseudo-second-order model ( R 2 = 0.990) and Langmuir isotherm model ( R 2 = 0.962), indicating it was a monolayer chemical adsorption process. The Cr(VI) removal was affected by pH and achieved the maximum when pH = 3.0, which may be ascribed to the better corrosion of nZVI and release of Fe(II) from the S-nZVI@PBC in acidic condition. The primary mechanisms were adsorption, reduction, and co-precipitation. S-nZVI@PBC exhibited higher stability and reusability than nZVI, which makes it more promising in environmental application. Overall, S-nZVI@PBC is of great potential for treating Cr(VI)-containing wastewater.